The research trends and contributions of System's publications over the past four decades (1973–2017): A bibliometric analysis. (February 2019) - Lei, Lei; Liu, Dilin
Abstract: Using the System journal's bibliometric data from 1973 to 2017, this study investigated the journal's research themes and their evolving patterns over four decades divided into three periods. Specifically, the study identified and examined the journal's most frequently discussed topics, its most highly cited articles, and the most highly cited references and authors in the journal. The results show that the journal's publications have focused on foreign and second language learning/teaching practice issues, particularly the use of learning strategies and technology, while successfully keeping pace with the new developments in theory and practice in the field of applied linguistics, especially the developments in research on socio-cultural and socio-psychological issues. The results also reveal some areas where the journal may need to focus more on or make some adjustments in order to further enhance its success in achieving its declared aims and scopes, i.e., its missions.